Helping Patients Choose Their Ideal Treatment for Achilles Tendon Ruptures: A Network Meta-Analysis and Protocol for Development and Field Testing a Patient Decision Aid - Meulenkamp, Brad (Université d'Ottawa / University of Ottawa, 2021)
Treatment of acute Achilles tendon ruptures has long been controversial. Several treatment options exist for patient with variable harms and benefits to each. Recognizing that decision of treatment option is preference-sensitive, this thesis focused on updating the current literature on Achilles tendon rupture management to facilitate the creation of a patient decision aid. A network meta-analysis of all treatment options for acute Achilles tendon ruptures was performed. Results demonstrated that minimally invasive surgery options were associated with lower complications and lower complications requiring surgery. Return to sport was similar amongst all treatment groups. With guidance from the Ottawa Decision Support Framework and the International Patient Decision Aid Standards, a three-tiered protocol for development, alpha testing and field-testing a novel patient decision aid is outlined next. The patient decision aid will be reviewed and revised iteratively by multi-disciplinary steering group. This protocol will act as a framework for further orthopaedic patient decision aid development.
Keywords: Achilles tendon; Patient decision aid; Network meta-analysis